Association between cardiovascular health and metabolic dysfunction-associated steatotic liver disease: a nationwide cross-sectional study - Lian-Zhen Huang; Ze-Bin Ni; Wei-Feng Huang; Li-Ping Sheng; Yan-Qing Wang; Jin-Yan Zhang (Journal of Health, Population and Nutrition)
Abstract Purpose Evidence concerning the effect of cardiovascular health (CVH) on the risk of metabolic dysfunctional-associated steatotic liver disease (MASLD) is scarce. This study aimed to investigate the association between CVH and MASLD. Methods 5680 adults aged ≥ 20 years from the National Health and Nutrition Examination Survey 2017-March 2020 were included. Life’s essential 8 (LE8) was applied to assess CVH. Weighted binary logistic regression was employed to calculate the odds ratio (OR) and 95% confidence interval (CI) to investigate the association of CVH with MASLD. Restricted cubic spline (RCS) was conducted to explore the dose-response association between LE8 and its subscales scores with MASLD. Results Among 5680 participants, 724, 3901, and 1055 had low, moderate, and high CVH levels, respectively, with a MASLD diagnosis prevalence of 36.83%. In the fully adjusted logistic regression model, ORs for MASLD were 0.50 (95% CI, 0.37–0.69) for participants with moderate CVH and 0.21 (95% CI, 0.13–0.34) for those with high CVH, when compared to those with low CVH (P < 0.001 for trend). OR for MASLD was 0.68 (95% CI, 0.61–0.77) for each 10-point increase in LE8 score. RCS model demonstrated a non-linear dose-response relationship between LE8 score and health factors score with MASLD, while a linear relationship was found between health behaviors score and MASLD. Subgroup analysis showed a consistent negative correlation between LE8 score and MASLD, and sensitivity analysis validated the reliability of these findings. Conclusions Higher LE8 score was associated with a lower risk of MASLD. Encouraging adherence to optimal CVH levels may help mitigate the burden of MASLD.